Zinc: an undervalued microelement in research and treatment - Hawrysz, Zofia; Woźniacka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Recent years have seen a growing interest in a healthy lifestyle, particularly nutrition. An important component of a balanced diet is the microelement content. Zinc is the second most abundant trace element, after iron. It has antioxidant and immunomodulatory functions, and plays important roles in the pathogenesis of various diseases, including dermatoses. Individuals with a zinc deficiency may present with nonspecific erythematous, pustular, erosive, and bullous lesions as well as alopecia, nail dystrophy, and a variety of systemic symptoms. Any individual assessment of zinc levels should consider risk factors for deficiency, clinical symptoms, type of diet, and results of laboratory analyses. Recent research has shed light on the systemic and topical effects of zinc, indicating the value of its supplementation for many conditions.